LITERATURE REVIEW: A ROLE OF QUALITY OF WORK LIFE AND EMOTIONAL INTELLIGENCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOUR AMONG Z-GENERATION WORKER - Mhakarya, Chandra (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to explore the literature on the role of Human Resources (HR) within organizations, particularly in the context of new generations such as Generation Z. This study also seeks to analyze the relationship between Quality of Work Life (QWL), Emotional Intelligence (EI), and Organizational Citizenship Behavior (OCB). Method: This research employs a literature review approach to analyze secondary data from existing studies, articles, and reports. The data are categorized and summarized to understand how Quality of Work Life (QWL) and Emotional Intelligence (EI) impact Organizational Citizenship Behavior (OCB) among Gen-Z workers. The study aims to identify patterns, gaps, and insights to help organizations foster OCB in Gen-Z employees across various settings. Results: Both Quality of Work Life (QWL) and Emotional Intelligence (EI) significantly influence Organizational Citizenship Behavior (OCB) among Gen Z workers. A positive QWL, including fair compensation, a supportive environment, and work-life balance, motivates Gen Z employees to go beyond basic job expectations. High EI enhances OCB by helping employees manage emotions, fostering better interpersonal relationships, teamwork, job satisfaction, and increased productivity. Novelty: The novelty of this research lies in its focus on the emerging Generation Z in the workplace, exploring how their distinct characteristics and expectations interact with key organizational factors like Quality of Work Life (QWL), Emotional Intelligence (EI), and Organizational Citizenship Behavior (OCB). While existing studies have explored these individual factors, this research brings a fresh perspective by examining how they collectively impact employee performance and well-being in the modern, multigenerational workplace.